Temporal Dynamics of the Resistome of the Intestinal Microbiota of a Healthy Population against the Background of COVID-19 - A. V. Pavlenko; A. I. Manolov; Yu. I. Esin; A. L. Arkhipova; A. V. Vvedenskiy; A. V. Kudryavtsev; E. A. Krieger; L. L. Shagrov; N. I. Belova; E. N, Ilyina (Антибиотики и Химиотерапия, 2024)
Background. Antibiotics were widely used during the COVID-19 pandemic, which may have led to an increase in the number and diversity of antibiotic resistance genes. Most studies assessing the human resistome during this period were conducted over a short period of time and on diﬀerent cohorts of people. In this case, the most informative approach is to study the composition of the resistome in people who have and have not recovered from COVID-19, using paired stool samples obtained before and after the pandemic.The aim of the study was to assess the prevalence of antibiotic resistance genes in the intestinal microbiota of the adult population of Arkhangelsk city before and after the COVID-19 pandemic.Material and Methods. The study included a random population sample of residents of Arkhangelsk who provided paired stool samples at intervals of ﬁve years. The study procedure included surveying and identiﬁcation of antibiotic resistance genes in stool samples using polymerase chain reaction. Processing of the obtained data was carried out in the R language.Results. The samples of almost all participants contained genes that cause resistance to macrolides: mefA and ermB. The frequency of glycopeptide resistance genes (vanA and vanB) in post-pandemic samples decreased signiﬁcantly. There is a trend towards an increase in the number of antibiotic resistance genes among patients hospitalized for COVID-19 compared to outpatients. The proportion of macrolide resistance genes shifted toward an increased relative representation of mefA in post-pandemic samples.Conclusion. The resistome of study participants did not undergo signiﬁcant changes during the COVID-19 pandemic, except for a decrease in the prevalence of glycopeptide resistance genes and a change in the ratio of macrolide resistance genes.